Risk and outcome of nosocomial Staphylococcus aureus bacteraemia in nasal carriers versus non-carriers. - Wertheim, H; Vos, M; Ott, A; van Belkum, A; Voss, A; Kluytmans, J; van Keulen, P; Vandenbroucke-Grauls, C; Meester, M; Verbrugh, H (2004)
Staphylococcus aureus is the second most frequent cause of nosocomial blood infections. We screened 14008 non-bacteraemic, non-surgical patients for S aureus nasal carriage at admission, and monitored them for development of bacteraemia. Nosocomial S aureus bacteraemia was three times more frequent in S aureus carriers (40/3420, 1.2%) than in non-carriers (41/10588, 0.4%; relative risk 3.0, 95% CI 2.0-4.7). However, in bacteraemic patients, all-cause mortality was significantly higher in non-carriers (19/41, 46%) than in carriers (seven/40, 18%, p=0.005). Additionally, S aureus bacteraemia-related death was significantly higher in non-carriers than in carriers (13/41 [32%] vs three/40 [8%], p=0.006). S aureus nasal carriers and non-carriers differ significantly in risk and outcome of nosocomial S aureus bacteraemia. Genotyping revealed that 80% of strains causing bacteraemia in carriers were endogenous.